2003
DOI: 10.1016/s0002-9440(10)63492-x
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Sulfatase and Estrogen Sulfotransferase in the Atherosclerotic Human Aorta

Abstract: Various epidemiological studies have demonstrated a relatively low incidence of cardiovascular events in premenopausal women and its marked increment after menopause. In addition, estrogens have been postulated to exert direct anti-atherogenic effects via binding to estrogen receptors in vascular smooth muscle cells (VSMCs). However, not all postmenopausal women develop atherosclerosis despite decreased levels of serum estrogen. Therefore, we believe it is important to examine the status of estrogen metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 68 publications
(80 reference statements)
3
33
0
Order By: Relevance
“…It has been reported that the amounts of steroidogenic enzymes related to in situ estrogen production were significantly higher in female aorta than that in male aorta [10,14]. Results of our present study also indicated that this intracrine mechanism enhances or facilitates steroid hormone effects in human aorta especially in female.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…It has been reported that the amounts of steroidogenic enzymes related to in situ estrogen production were significantly higher in female aorta than that in male aorta [10,14]. Results of our present study also indicated that this intracrine mechanism enhances or facilitates steroid hormone effects in human aorta especially in female.…”
Section: Discussionsupporting
confidence: 78%
“…Both steroidogenic endocrine glands and local synthesis are currently considered to contribute to the pool of progesterone present in brain and peripheral nerves. We previously demonstrated in situ estrogen synthesis in human aorta, especially in female aorta [10]. It has also been reported that progesterone plays an important role in athero-protection in human VSMCs via progesterone receptors (PRs) [16], in the same fashion as estrogen via estrogen receptors (ERs).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations